Trees as hotspots: Using forests, trees, and agroforestry to foster diverse sustainable landscapes - Gitz, V.; Xu, J.; Lu, Y.; Springgay, E.; Animon, I.; Mubarak, R.K.A.; Nasi, R.; Simons, T.; Barthakur, R.; Wang, R.; Su, J.; Sinclair, F.; et al. (Maximum Academic Press, 2022)
Forests, trees, and agroforestry (FTA) are ecosystem hotspots. They exemplify the contributions of biodiversity to sustainable and resilient landscapes, green circular economy and to sustainable agriculture and food systems for healthy diets. However, most research on these topics have been performed separately and lack comparison. The International FTA-Kunming Conference 'Forests, trees and agroforestry for diverse sustainable landscapes' 22nd–24th June 2021, focused on these contributions, brought together scientists NGOs, and policy makers to further the understanding of tree diversity; provided a communication platform for scientists to share their research results; evaluated the role of tree diversity in agroecology and circular agriculture; assessed benefits of landscape restoration; and explored applied research in mountain ecosystems and food security. The goals were to gather evidence that ground the design of solutions that can contribute to the implementation of the post 2020 Global Biodiversity Framework and towards the UN Food Systems Summit, and the overall implementation of the SDGs. This paper summarizes the outcomes of the international FTA Conference in Kunming 2021 and points out the highlights of research involved in six major themes.